Functional Variables and Enzyme (CPK)to Skill of The main and Alternatives Players in Football (comparative study) - Majed Sabar Mohammed1 , Ali Sabar Mohammed2 , Emad Khadim Abed Al-kaabi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Football is a type of sport that attracts people’s attention. So, it is necessary to look for everything thatcan improve its reality and develop it. The importance of this research paper is to have a look on theimpact of competitions on functional devices, enzyme (CPK), aspects and the skills for the main players andcompared with the substituted players in football. The study aims at identifying the level of some functionalvariables, enzyme (CPK) and the skills for key players and substituted players in football; identifying thedifferences in some functional variables, enzyme (CPK) and the skills of the key and substituted playersin football. Descriptive method is used by researchers in a comparative way to solve the problem of thestudy. The number of sample is fifteen players distributed to two groups, the first group is the key players[9] and the second group is substituted players [6]. Also, the researchers used the SPSS statistical systemto extract the results of the tests. The most important conclusions are: (1) competitions play an active rolein developing the performance level, whether at the functional level or enzyme CPK or skills. (2) The roleof CPK enzyme has increased after performing high physical effort and for a long time for the key playersas a result of competition effort. Moreover, the following is the most important recommendations that thestudy has reached into: (1)It is necessary to participate all players in the competition, even periodically, sothat substituted player can sense the atmosphere of competition and his active role in the development offunctional and skills of the player .